The Effect of Catholic Religion on Dayak Identity in West Kalimantan - Kristianus Kristianus (STKIP Singkawang, 2022)
The background of this research is the issue of ethnic identity in West Kalimantan, where religion is associated with ethnic identity. This study used the ethnographic method by interviewing 26 Catholic religious leaders and community leaders for three months. The data analysis used in this study was a qualitative descriptive analysis. The data that had been collected based on observations, interviews, and documentation were analyzed and described critically. The research findings showed that the thesis that said Dayak identity was influenced by the Dutch colonial was not fully accepted. The formation of Dayak identity was actually influenced by Catholicism. The names of the inhabitants used the names of Catholic saints. The use of language, dance, and symbols with Dayak nuances carried out in Catholic religious rituals attracts the Dayak people to embrace Catholicism. The Dayak language as a medium of communication had been used by Catholicism, not only for singing texts but also for the entire series of ritual ceremonies to the most sacred expressions of prayer. This research is still far from perfect, but the results can at least be used as a dialectic for academic discussions about Dayak identity. Some data sources are still in Dutch, so they can only be understood in a limited way, for it is recommended that in further research these documents can be translated first.